Comparative study on growth and morphological characteristics of a wild type strain Rhizobium spp. (RCA-220) and a genetically engineered E. coli BL21 (Journal of Bio-Science, 2014)
Context: Comparison between a wild type strain Rhizobium spp. (RCA-220) and a genetically modified strain E. coli BL21 in context of growth features. Objective: To observe the comparative growth characteristics of a genetically modified E. coli BL21 and an isolated wild type strain Rhizobium spp. (RCA-220). Materials and Methods: Different kinds of investigations were accomplished in both Luria-Bertani (LB) liquid and semi-solid media to observe the growth and maintenance of these strains. For the isolation of Rhizobium spp. selective Yeast Extract Manitol Agar (YEMA) was used. Colony morphology, pH, temperature, carbon source, salt concentration and light were taken under consideration and optimized for growth characteristics. Results: For the strain E. coli BL21, the maximum growth rate was 1.9 at incubation time 72 h, pH 7.2, temperature 37°C (optimized) while for Rhizobium spp. the growth rate was significantly higher (OD 2) at pH 6.8, temperature 28°C (optimized). Among all used carbon sources, strains grown in the medium supplemented with peptone showed rapid and good performance. So, peptone was proved as the best carbon source for both strains. The maximum growths of these strains were observed at 0g/100ml NaCl salt concentration. RCA-220 strain was comparatively more tolerable to salt than E. coli BL21 strain. In this work, E. coli BL21 showed rapid and good performance in presence of light while Rhizobium spp. showed better performance in absence of light. Statistical analysis showed that the growth rate of Rhizobium spp. was significantly higher than E. coli BL21. Conclusion: From the experimental results, it can be concluded that naturally obtained microbial strains were stable and could tolerate any stress condition where the modified strains lose their growth capability and the overall growth performances were reduced or slowed down than the wild type strain. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17718 J. bio-sci.  20:  75-82, 2012